Conflict management in family businesses: A bibliometric analysis and systematic literature review. Issue 4 (13th August 2018) - Caputo, Andrea; Marzi, Giacomo; Pellegrini, Massimiliano Matteo; Rialti, Riccardo
Abstract : Purpose: The purpose of this study is to map the intellectual structure of the field of conflict management and the field of family business to the investigation of conflicts in family firms, with the aim of contributing to the further integration of knowledge between the two fields. Design/methodology/approach: Family conflicts and work–family balance issues also received a lot of attention, yet studies in conflict management still seem to overlook a thorough investigation of conflict in family businesses. Conflict is a major aspect of family businesses, which differs highly from non-family businesses, and offers an important research avenue for conflict management scholars to contribute to the investigation of major characteristics of organisations that constitute a large part of the value created in the world. Findings: The results of a bibliometric analysis and systematic literature review show that studies concerning conflict in family business aggregate around three clusters: organisational conflicts; firm growth and conflicts; and family control, performance and conflicts. An interpretative framework is also developed to interpret how antecedents, conflicts and growth dynamics in family business influence performances. Findings show how family conflicts and work–family balance issues received a lot of attention, yet studies in conflict management still seem to miss a thorough investigation of conflict in family businesses. Originality/value: This paper contributes to the field of conflict management and family business by providing a systematic analysis of knowledge and family firms. This paper can be a starting point for researchers interested in understanding how conflicts affect family businesses.